John Stuart Mill Felsefesinde Kadının Toplumdaki Yeri - Durhan, Gülümser (Muş Alparslan Üniversitesi, 2015)
Woman's position in society is a problem rather than a phenomenon in the Mill’s Philosophy. This is the problem of marginalized women which depending on gender discrimination. This problem is harmful to both men and women. It is one of the biggest obstacles in front of the development of humanity. According to Mill this problem can solve with a layout that provides equal rights for everyone and none of the man or woman is a privilege or power over the other is not entitled to use. The aim of this study is to analyze that how male is dominant over women and marginalized position of women in society in Mill's Philosophy.Keywords: John Stuart Mill, Women, Men, Othering, Dependence.

Mill Felsefesinde kadının toplumdaki yeri, bir olgudan ziyade bir problemdir; cinsiyet ayrımına bağlı olarak ortaya çıkan kadının ötekileştirilmesi problemidir. Hem kadın hem erkek için ve dolayısıyla toplum için zararlı olan bu sorun, insanlığın gelişiminin önündeki en büyük engellerden biridir. Mill’e göre bu sorun ancak kadın ya da erkeğin; hiçbirinin diğeri üzerinde bir ayrıcalık ya da güç kullanma hakkına sahip olamayacağı, diğerinin de hiçbir yoksunluk hissetmeyeceği; herkese eşit haklar sağlayan bir düzen ile çözülebilir. Dolayısıyla bu çalışmadaki amacımız, Mill Felsefesinde erkeğin kadın üzerinde nasıl baskın olduğunu açıklamak ve ötekileştirilmiş kadının toplumdaki yerini analiz etmektir.Anahtar Kelimeler: John Stuart Mill, Kadın, Erkek, Ötekileştirme, Bağımlılık.
According to the Mill’s Philosophy Woman's Position in Society
anemon